Negative urgency and emotion regulation predict positive smoking expectancies in non-smoking youth. (July 2016) - Dir, Allyson L.; Banks, Devin E.; Zapolski, Tamika C.B.; McIntyre, Elizabeth; Hulvershorn, Leslie A.
Abstract: Introduction: The purpose of the study was to better understand early risk for positive smoking expectancies, which have been shown to be consistent predictors of smoking initiation among youth. Two affect-based risk factors—negative urgency and emotion dysregulation—associated with smoking behaviors among youth, were examined for unique and interactive effects on positive smoking expectancies among substance-naïve youth. Methods: Participants were 61 10–14-year-old children with virtually no drug use (less than 5 substance use incidents across the lifetime), who were drawn from the community. Results: Both negative urgency and emotion dysregulation were significantly associated with positive social facilitation smoking expectancies. Further, negative urgency was significantly related to positive social facilitation smoking expectancies at higher levels of emotion dysregulation ( b = .09, p = .001). Conclusion: The findings provide evidence that both emotion dysregulation and negative urgency are positively associated with positive social-related smoking expectancies among a sample of 10–14-year-olds. Children who are emotionally dysregulated and who act rashly in response to negative emotions appear more likely to endorse beliefs regarding the socially enhancing effects of smoking, suggesting that these youth may be at high risk for smoking initiation. Highlights: Positive smoking expectancies were explored among substance-naïve children. Negative urgency and emotion dysregulation were uniquely related to expectancies. Emotion dysregulation moderated the effect of negative urgency on expectancies. Youth high on both traits may be at higher risk for smoking initiation.